The role of probiotics, prebiotics, and synbiotics in the treatment of inflammatory bowel diseases: an overview of recent clinical trials - Yassine, Fayez; Najm, Adam; Bilen, Melhem (Frontiers in Systems Biology, 2025)
BackgroundThe increasing incidence of inflammatory bowel diseases (IBD) over the last two decades has prompted the need to create new types of therapeutic interventions. The gut microbiome has emerged as a key component in the prognosis and pathophysiology of IBDs. The alteration or dysbiosis of the gut microbiome has been shown to exacerbate IBDs. The bacterial composition of the gut microbiome can be modulated through the usage of probiotics, prebiotics, and synbiotics. These interventions induce the growth of beneficial bacteria. Additionally, these interventions could be used to maintain gut homeostasis, reduce the inflammation seen in these morbidities, and strengthen the gut epithelial barrier.MethodsThe literature review was conducted in October 2024 using PubMed, Scopus, and Google Scholar screening for recent clinical trials in addition to reviews relevant to the topic.AimsThis review aims to summarize the recent clinical trials of probiotics, prebiotics, and synbiotics in IBD patients highlighting their potential benefits in alleviating symptoms and enhancing the quality of life.ConclusionCertain probiotic formulations such as single strain ones consisting of Lactobacillus, or mixed-strain combinations of Lactobacillus and Bifidobacterium, prebiotic compounds such as fructooligosaccharides, and synbiotic combinations of both have proven effective in improving the clinical, immunological, and symptomatic aspects of the disease course. While promising, these findings remain inconclusive due to inconsistent study designs, small sample sizes, and varying patient responses. This emphasizes the need for larger, well-controlled trials to determine their clinical efficacy.